Cor-triatriatum A Rare Congenital Heart Disease Presented in Adulthoodsurgical treatment in Apollo Hospitals Dhaka - Zahangir, NM; Kabir, AHM L; Ahmed, F; Ahmad, ST; Hossain, M; Hossain, N; Rahman, MS; Khan, MMH; Talukder, MQI (Pulse, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/pulse.v5i2.20268 Pulse Vol.5 July 2011 p.58-60